2019
DOI: 10.1186/s13030-019-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in oral health related quality of life among the elderly: a randomized controlled trial

Abstract: BackgroundThe present study was conducted to determine the impact of educational intervention based on adult learning theory on oral health related quality of life of the elderly.Materials and methodsThis study (IRCT20120910010804N13) was performed with 92 elderly patients referred to the dental clinic of Ahvaz Jundishapur University of medical sciences. Participants were randomly divided into experimental and control groups. The data were gathered by a questionnaire with demographic variables, variables of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
(44 reference statements)
0
10
0
5
Order By: Relevance
“…The results showed that the educational program alongside therapeutic interventions had a positive impact, which improved the oral health-related quality of life in the elderly ( p < 0.001). 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the educational program alongside therapeutic interventions had a positive impact, which improved the oral health-related quality of life in the elderly ( p < 0.001). 18…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the educational program alongside therapeutic interventions had a positive impact, which improved the oral health-related quality of life in the elderly (p < 0.001). 18 Oral health education is a part of health promotion programs in public health centers, which include various targets for different age groups. Health promotion strategies for the elderly have three basic outcomes: maintaining and increasing functional capacity, improving selfcare, and stimulating individual social networks.…”
Section: Discussionmentioning
confidence: 99%
“…15 Yulinda dkk 17 , mengatakan penyuluhan menggunakan metode ceramah dan media video dalam penyuluhan kesehatan efektif dalam meningkatkan sikap responden ke arah sikap yang lebih baik. 17,26,27 Haris dkk 14 , mengungkapkan penyuluhan dengan menggunakan video tidak dapat berjalan atau berdiri sendiri melainkan masih memerlukan metode lainnya seperti ceramah, diskusi dan sebagainya. Keberhasilan penyuluhan kesehatan pada masyarakat tergantung kepada komponen pembelajaran.…”
Section: Pembahasanunclassified
“…Goal kesehatan termasuk konsep yang multidisiplin termasuk fisik, psikologis, sosial, mental dan gejala terkait penyakit atau perubahan dalam perawatan. (Shokouhi et al, 2019) Usia lanjut terkait dengan perubahan fisiologis, nafsu makan menurun, masalah nutrisi, masalah gigi dan mulut seperti kehilangan gigi, sulit menelan dan mengunyah makanan, diikuti dengan beberapa penyakit kronis. Fenomena bertambahnya usia menambah beban semua penyakit kronis, termasuk penyakit gigi dan mulut.…”
Section: Gambar 4 Video Edukasi Mencuci Tangan Dari Rsgm Fkg Updmbunclassified
“…Kualitas hidup terkait kesehatan rongga mulut adalah bagaimana seseorang menilai status mental, psikologis, status sosial yang dipengaruhi oleh kesehatan rongga mulutnya. (Shokouhi et al, 2019) Populasi geriatri dapat dibagi menjadi 3 kelas, dalam hal melakukan perawatan kesehatan gigi dan mulut, diantara yaitu : 1) Lansia yang mandiri secara fungsional. Mereka memiliki kemampuan mengemudi dan / atau menggunakan transportasi umum sendiri untuk Jurnal Abdi MOESTOPO ISSN: 2599-249X -Vol.…”
Section: Gambar 4 Video Edukasi Mencuci Tangan Dari Rsgm Fkg Updmbunclassified